2022
DOI: 10.3390/cancers14122850
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Vinflunine for Patients with Metastatic Urothelial Cancer after Immune Checkpoint Inhibitor Pretreatment—A Retrospective Multicenter Analysis

Abstract: Background: Immune checkpoint inhibitors (ICI) are standard of care in patients with metastatic urothelial carcinoma (mUC) ineligible for cisplatin, and as second-line therapy after platinum-based chemotherapy. To date, few data exist about the efficacy of the former second-line chemotherapeutic agent vinflunine after the failure of sequential platinum-based chemotherapy and ICI treatment. The aim of this analysis was to examine the efficacy of vinflunine in a post-ICI third- or later-line setting. Methods: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…Interestingly, most recent studies showed favourable efficacy of chemotherapy after progression of ICI or EV [30,33,34], suggesting chemotherapy remains important even in the new era of immune and targeted treatments. Sequential use of these different therapies would provide the best chance of survival.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, most recent studies showed favourable efficacy of chemotherapy after progression of ICI or EV [30,33,34], suggesting chemotherapy remains important even in the new era of immune and targeted treatments. Sequential use of these different therapies would provide the best chance of survival.…”
Section: Discussionmentioning
confidence: 99%